Deklarowane przekonania dotyczące uczenia się matematyki w czasach szkolnych przez kandydatki i kandydatów na nauczyciel(k)i edukacji wczesnoszkolnej - Adam Mroczkowski (Problemy Wczesnej Edukacji)
The article presents the results of the study of declared beliefs regarding learning mathematics in school times by students of three consecutive years of the preschool and early school pedagogy. The empirical material was collected using an authorial questionnaire. Most of the people participating in the study declared, among other things, that the most effective strategy in the times of school education was learning mathematics by heart, and the key reason for possible failures is the lack of mathematical talent. The article also reflects on minimizing the transfer of such beliefs by students to future teaching practice.